Comment on 'The relativistic Aharonov-Bohm-Coulomb system with position-dependent mass' - Mendrot, V. B. [UNESP]; Castro, A. S. de [UNESP] (Iop Publishing Ltd, 2021)
It is shown that the paper 'The relativistic Aharonov-Bohm-Coulomb system with position-dependent mass' recently published in this journal has fulcrum on false assertions.
Keywords: Dirac equation; chiral projectors; chirality operator